Determinan Minat Penggunaan Kontrasepsi IUD Pada Wanita Usia Subur : Peran Pengetahuan, Persepsi Efek Samping dan Dukungan Suami - Rini Mayasari; Zurizah, Yuhemy; Leny (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
The use of intrauterine devices (IUDs) in Indonesia remains relatively low compared to short-term contraceptive methods, although IUDs are effective and safe long-term contraceptive methods. Low interest in IUD use is influenced by several factors, including knowledge, perceptions of side effects, and husband support. This study aimed to analyze the determinants of interest in using IUD contraception among women of reproductive age based on knowledge, perception of side effects, and husband support at Puskesmas X Palembang City in 2026. This study employed an observational analytic design with a cross-sectional approach. The study population consisted of women of reproductive age in the working area of Puskesmas X Palembang City. A total of 180 respondents were selected using accidental sampling techniques. Data were collected using structured questionnaires that had been tested for validity and reliability. Data analysis included univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using multiple logistic regression with a 95% confidence level (α = 0.05). The results showed that most respondents had good knowledge (56.7%), positive perceptions regarding IUD side effects (53.3%), received husband support (61.1%), and were interested in using IUD contraception (57.8%). Bivariate analysis showed significant relationships between knowledge and interest in IUD use (p-value = 0.001), perception of side effects and interest in IUD use (p-value = 0.002), and husband support and interest in IUD use (p-value = 0.000). Multivariate analysis revealed that husband support was the most dominant factor influencing interest in IUD use with an OR value of 4.562. Knowledge, perception of side effects, and husband support were significantly associated with interest in IUD contraceptive use. Husband support was the dominant factor influencing women’s interest in using IUD contraception.